ROLE OF ECDYSTEROIDS ON THE DETERMINATION AND TIMING OF GUT PURGE IN THE LAST LARVAL INSTAR OF SPODOPTERA MAURITIA BOISD. (LEPIDOPTERA : NOCTUIDAE) - BALAMANI, E.; NAIR, V.S.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
Neck-ligated and thorax-ligated sixth (final) instar larvae of Spodoptera mauritia Boisd. of known ages (day 1, 2 and 3) were injected with 1 µg or 3 µg ecdysterone and the effects of these treatments on the gut purge behaviour were studied. Ligated day 1 and day 2 larvae kept as controls showed a complete inhibition of gut purge behaviour. On the other hand injection of ecdysterone to ligated larvae inducted gut purge. Ligated day 3 larvae injected with ecdysterone showed a remarkable acceleration in the timing of gut purge behaviour when compared to controls. The significance of these findings is discussed.